Arsenic hyperaccumulation and speciation in the edible ink stain bolete (Cyanoboletus pulverulentus) - Braeuer, Simone; Goessler, Walter; Kameník, Jan; Konvalinková, Tereza; Žigová, Anna; Borovička, Jan (Food chemistry, 2018)
The edible ink stain bolete (Cyanoboletus pulverulentus) was found to hyperaccumulate arsenic. We analyzed 39 individual collections determined as C. pulverulentus, mostly from the Czech Republic. According to our results, concentrations of arsenic in C. pulverulentus fruit-bodies may reach 1300mgkg-1 dry weight. In most collections, data for total and bioavailable arsenic in underlying soils were collected but no significant correlation between the soil arsenic content and arsenic concentrations in the associated fruit-bodies was found. Within the fruit-bodies, we found the majority of arsenic accumulated in the hymenium. Besides occasional traces of methylarsonic acid (MA), the arsenic speciation in all mushroom samples consisted solely of dimethylarsinic acid (DMA) and no inorganic arsenic was detected. Because of the carcinogenic potential of DMA, C. pulverulentus should not be recommended as an edible mushroom and its consumption should be restricted.
Keywords: Dimethylarsinic acid; HPLC-ICPMS; kyselina kakodylová; Basidiomycota; Soil Pollutants; Edible mushrooms; arsenikové přípravky; Cacodylic Acid; Czech Republic; arsen; Health risk; Česká republika; Soil; Arsenicals; látky znečišťující půdu; kontaminace potravin; Food Contamination; Arsenic